Benchmarking of mobile apps on heart failure - Virna Ribeiro Feitosa Cestari; Raquel Sampaio Florêncio; Thiago Santos Garces; Vera Lucia Mendes de Paula Pessoa; Thereza Maria Magalhães Moreira (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to analyze the mobile apps on heart failure available in the main operating systems and their usability. Methods: benchmarking of mobile applications, systematic research, comprising 38 mobile applications for analysis of general information, functionalities and usability. Usability was assessed using System Usability Scale and Smartphone Usability Questionnaire, followed by the calculation of the agreement index and the exact binomial distribution test, with a significance level of p> 0.05 and a proportion of 0.90. Results: mobile applications had English as the predominant language (73.7%), were directed to patients (71.1%) and the predominant theme was disease knowledge (34.2%). Functionalities ranged from general features to the need for an internet connection. In assessing usability, heart failure was shown to be 92.1% -94.7% and p <0.05. Final considerations: the mobile apps on heart failure have varied content and adequate usability. However, there is a need to develop more comprehensive mobile applications.